Chinese Aid to Africa: Distinguishing Features and Local Effects - Ann-Sofie Isaksson; Andreas Kotsadam (Research Institute of Industrial Economics (IFN), 2020)
Drawing on our recent work on local effects of Chinese development projects in Africa, this review article highlights a number of distinguishing features of Chinese aid, and discusses how these may translate into local aid impacts that differ from those of other donors. Unlike aid from other major donors, Chinese aid projects were found to fuel local corruption, discourage trade union involvement, to not increase political incumbency support, and to make ethnic identities more salient in the local areas. As such, our findings highlight important donor heterogeneities as well as the need to consider not only to what extent aid achieves its explicit objectives, but also its potential unintended effects, or externalities.
Keywords: F35; O19; O55; 330; China; Africa; Foreign aid